2019
DOI: 10.1038/s41433-019-0510-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an AI system for the automated detection of glaucoma from stereoscopic optic disc photographs: the European Optic Disc Assessment Study

Abstract: Objectives:To evaluate the performance of a deep learning based Artificial Intelligence (AI) software for detection of glaucoma from stereoscopic optic disc photographs, and to compare this performance to the performance of a large cohort of ophthalmologists and optometrists. Methods:A retrospective study evaluating the diagnostic performance of an AI software (Pegasus v1.0, Visulytix Ltd., London UK) and comparing it to that of 243 European ophthalmologists and 208 British optometrists, as determined in previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…Only eight studies 14 21 used prospectively collected data and 29 (refs. 14 , 15 , 17 , 18 , 21 45 ) studies validated algorithms on external datasets. No studies provided a prespecified sample size calculation.…”
Section: Resultsmentioning
confidence: 99%
“…Only eight studies 14 21 used prospectively collected data and 29 (refs. 14 , 15 , 17 , 18 , 21 45 ) studies validated algorithms on external datasets. No studies provided a prespecified sample size calculation.…”
Section: Resultsmentioning
confidence: 99%
“…Raghavendra et al 27 have achieved the highest accuracy of 98.13% using only 18 layers of CNN. Rogers et al 28 have evaluated the performance of a deep learning-based artificial intelligence software for detection of glaucoma from stereoscopic optic disc photographs in the European Optic Disc Assessment Study, and the system has obtained a diagnostic performance and repeatability comparable to that of a large cohort of ophthalmologists and optometrists. Shibata et al 16 have validated the diagnostic ability of the deep residual learning algorithm in highly myopic eyes which makes the detection of glaucoma a challenging task because of the morphological difference from those of non-highly myopic eyes.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][27][28][29] Although most of recent studies have been suggested numerous potential and vision in this field, various stages and structure-function correlations of the glaucoma have received little attention. The results of our study show agree with those found in earlier investigations with an accuracy of 83.4-98.1% 13,17,[27][28][29] and an AUROC of 0.887-0.996, 12,[14][15][16][17][18][19] and moreover this study enhanced the research by applying a third classification grade to the glaucoma severity based on functional tests. That third level of diagnostics can provide primary care with greater detail at an earlier stage improving the disease management, reducing the chances of blindness, and ultimately reducing the overall medical costs to the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system is designed to generalize to any fundus photograph that contains the optic disc, by first using a CNN to find and extract the optic nerve and then feeding a standardized image to another CNN that performs the classification. In a study by Rogers and colleagues, 55 the Pegasus AI system was compared to 243 European Ophthalmologists and 208 British optometrists in grading photographs for the presence of glaucomatous damage, achieving an overall accuracy of 83.4% and an area under the receive operating characteristic curve of 0.871, which was comparable to that of average ophthalmologists and optometrists.…”
Section: Introductionmentioning
confidence: 96%